Three-Dimensional-Printed Composite Scaffolds Containing Poly-ε-Caprolactone and Strontium-Doped Hydroxyapatite for Osteoporotic Bone Restoration - Codrea, Cosmin Iulian; Lincu, Daniel; Ene, Vladimir Lucian; Nicoară, Adrian Ionuț; Stan, Miruna Silvia; Ficai, Denisa; Ficai, Anton (Polymers, 2024)
A challenge in tissue engineering and the pharmaceutical sector is the development of controlled local release of drugs that raise issues when systemic administration is applied. Strontium is an example of an effective anti-osteoporotic agent, used in treating osteoporosis due to both anti-resorptive and anabolic mechanisms of action. Designing bone scaffolds with a higher capability of promoting bone regeneration is a topical research subject. In this study, we developed composite multi-layer three-dimensional (3D) scaffolds for bone tissue engineering based on nano-hydroxyapatite (HA), Sr-containing nano-hydroxyapatite (SrHA), and poly-ε-caprolactone (PCL) through the material extrusion fabrication technique. Previously obtained HA and SrHA with various Sr content were used for the composite material. The chemical, morphological, and biocompatibility properties of the 3D-printed scaffolds obtained using HA/SrHA and PCL were investigated. The 3D composite scaffolds showed good cytocompatibility and osteogenic potential, which is specifically recommended in applications when faster mineralization is needed, such as osteoporosis treatment.